Distribution of NH3 in the star forming region - Tileukulova, A.K.; Alimbetova, D.A.; Komesh, T.; Sailanbek, S.; Agishev, A.T. (Recent Contributions to Physics, 2021)
A multi-wavelength analysis of the large Galactic infrared bubble N 24 is has been presented in this paper in order to investigate the molecular and star formation environment around expanding H׀׀ regions. Using archival data from Herschel and ATLASGAL, the distribution and physical properties of the dust over the entire bubble are studied. To analyse the molecular environment in N 24, observations of NH3 (1,1) and (2,2) were carried out using the Nanshan 26-m radio telescope. The mass-size distributions of the clumps and the presence of massive young protostars indicate that the shell of N 24 is a region of ongoing massive star formation. We have presented a multi-wavelength investigation towards the large Galactic IR bubble N 24 to analyse the physical properties of the dust and gas therein. The infrared structure and the distribution of the molecular emissions show that the two main regions of G 19.07-0.28 and G 18.88-0.49 in the N 24 shell are consistent with star formation triggered by the expanding bubble. As a result of the feedback from massive stars, some new bubbles have already formed in these two regions, which further affect the environs therein. The data obtained was processed using the Gildas software package. We found that ammonia NH3 (1,1) and NH3 (2,2) are present in the N24 bubble region in the early stages of star formation.Key words: star formation, H׀׀ regions, N 24 bubble, molecular clouds, high-mass stars
Keywords: star formation; H׀׀ regions; N 24 bubble; molecular clouds; high-mass stars